Efektifitas Massage Perineum untuk Percepatan Persalinan Kala II pada Ibu Bersalin - Isofi Laspiriyanti; Lina Puspitasari (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
Background: Stiff perineum is caused by the nerves of the perineal muscle contain pyruvic acid which enters the mitochondria which are converted into lactic acid. Lactic acid causes metabolic problems and shrinks between the perineal muscle cells, so the perineum becomes stiff. The impact of a stiff perineum can inhibit the second stage of labor which increases the risk of death to the fetus and causes damage to the birth canal or laceration. Research Objectives: to accelerate the second stage of labor. Research Method: The design of this study uses the case study method. The sampling method used was non probability sampling through a purposive sampling approach of 3 patients. Patients used as participants were maternity patients in Cilacap District Hospital. Data was collected from January 2 to January 25, 2019. After tabulation with data that has been analyzed using analysis of explanation and time series. Results: The study showed there was a great impact of the Perineum Massage Midwifery Care for the Acceleration of Second Stage of Labor in Maternity Women. With the results of the first participant the process of accelerating labor took place within 15 minutes. In the second participant, the process of labor acceleration took place within 10 minutes. And in the third participant the process of accelerating labor took place within 20 minutes. Conclusion: Thus, that Perineum Massage Care for the Acceleration of Second Stage of Labor is really effective.